Nutritional behavior is a social and health problem in modern life style - N. S. , Akhmad; O, Ryspekova S.; Maral, Ergazina; A. M. , Orazymbetova; T. , Orazakiyeva; Y., Roslyakova; Nurgul, Darmen; Mussina; Zhunistaev; Jussipbekova (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to observe, analyze, compare and educate young people’s nutritional behavior. It was noticed that consumption of fruits and vegetables is low, restricted in many cases to one or two servings per day. This result led to the conclusion that healthy food does not play an important role in young people’s eating habits. Given this situation, in a few years childhood obesity rates could rise alarmingly. The nutrition factors contemplated were: the motivation of young people for a healthy diet; the information they possess about correct nutrition habits and their attitudes for a healthy lifestyle. In recent years, overweight and obesity have reached the status of a global pandemic and are particularly prevalent in the world. Overweight and obesity have been identified as risk factors for a number of health problems, including type 2 diabetes, hypertension, coronary heart disease and stroke. In recognition of the fact that reducing the burden of obesity and overweight has the potential to decrease mortality and disease worldwide, the World Health Organisation established that promoting healthy diets and physical activity is now a public health priority. This research paper aims to discuss the nutrition and health problem as well as eating behavior from the psychological aspects. This issue is very significant nowadays and considers to be the global problem. Here the authors made a research and analyses the background of this problem